Pengaruh Brand Image dan Brand Satisfaction Terhadap Brand Trust pada Mie Instan Merek Indomie - Dwi Sukmaning Ayu, Nandani; Arqy Ahmadi, Mirzam (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study aimms to explore the influence of brand image and brand satisfaction on brand trust in instant noodle products of the Indomie brand. The research method used is a qualitative approach, with data collection techniques through in-depth interviews with Indomie consumers. The results of the study indicate that a positive brand image, such as consistent product quality, attractive packaging, and a good reputation in the market, contribute significantly to building consumer trust in the Indomie brand. In addition, a high level of consumer satisfaction with the taste, quality, and price of the product also strengthens brand trust. This study reveals that brand image and brand satisfaction play an important role synergistically in shaping consumer trust. This study provides practical implications for manufacturers to continue to improve brand image and ensure consumer satisfaction, in order to maintain and increase customer loyalty. There are still shortcomings in this study, namely the lack of respondents interviewed, so the researcher hopes that further research can be better.